Agrarian south journal of political economy. - Centre for Agrarian Research and Education for South (New Delhi, India SAGE Publications, 2012)
The Journal aims to promote research on a variety of issues related to agrarian change, land use and global agriculture, while also contributing to the development of autonomous thinking in the South.
UP System perpetual contents: 2019
"A tri-annual journal of CARES."
Keywords: Agricultural innovations -- Periodicals; Agriculture and politics -- India -- Periodicals; Agriculture -- Economic aspects -- India -- Periodicals; Political Economy